State-Religious Relations in Azerbaijan During the Soviet Era - Mammadov, Jeyhun (Scholarya Demo Journal of Ruby, 2019)
The article covers the state-religious relations in Azerbaijan in Soviet era and the state policy implemented in this area. This period was one of the most difficult stages in the history of Azerbaijan. The activities of the places of religious worship were banned, the overwhelming majority of them were destroyed, and clergies were killed. It is reported that new legislative acts had been developed to regulate state-religious relations, a number of state structures had been created, and control over this area had been further strengthened. It is noted that clergies did not accept the annexation of Azerbaijan by Russia and rose up for fight. In subsequent years, closer to the fall of the Soviet Union, attitude towards religion had changed, a number of concessions had been applied. At the end of 1928, a new stage in the struggle against religion started in Azerbaijan, the work of mosques was suspended, and multiple worship centers were turned into clubs and other cultural and educational institutions. After the German invasion of the Soviet Union in 1941, the Soviet regimebecame more loyal to Islam, seeing that German troops showed good attitudetowards Islam during the occupation of the North Caucasus, and some German generals, arriving in the occupied territories of the North Caucasus, even converted to Islam and performed namaz in mosques. In March 1985, after the election of M.S.Gorbachev as General Secretary of the Central Committee of the CPSU, he started the policy of “restoration” and the attitude towards Islam relented; a number of books on Islam were prepared. It is emphasized that the Azerbaijani people did not abandon their traditions and religious beliefs despite all the attempts of the Soviet government. They managed to preserve their national mentality and moral values. It is noted that after the restoration of state independence of Azerbaijan, the prohibitions and restrictions applied for many years were ceased, the citizens’ freedom of religion and conscience was ensured, the conditions were created for the activities of religious organizations and the performance of religious rites.